Cybersecurity capacity-building: cross-national benefits and international divides. Issue 2 (4th May 2021) - Creese, S.; Dutton, W. H.; Esteve-González, P.; Shillair, R.
ABSTRACT: The growing centrality of cybersecurity has led many governments and international organisations to focus on building the capacity of nations to withstand threats to the public and its digital resources. These initiatives entail a range of actions that vary from education and training to technology and related standards, as well as new legal and policy frameworks. While efforts to proactively address security problems seem intuitively valuable, they are new, meaning there is relatively little research on whether they achieve their intended objectives. This paper takes a cross-national comparative approach to determine whether there is empirical support for investing in capacity-building. Marshalling field research from 73 nations, the comparative data analysis: (1) describes the status of capacity-building across the nations; (2) determines the impact of capacity-building when controlling for other key contextual variables that might provide alternative explanations for key outcomes and (3) explores the factors that are shaping national advances in capacity-building. The analysis finds a low, formative status of cybersecurity capacity in most of the nations studied and also shows that relatively higher levels of maturity translate into positive outcomes for nations. The study provides empirical support to international efforts aimed at building cybersecurity capacity.